Soviet and kosher : Jewish popular culture in the Soviet Union, 1923-1939 - Shternshis, Anna (Indiana University Press, 2006)
Kosher pork -- an oxymoron? Anna Shternshis's fascinating study traces the creation of a Soviet Jewish identity that disassociated Jewishness from Judaism. The cultural transformation of Soviet Jews between 1917 and 1941 was one of the most ambitious experiments in social engineering of the past century. During this period, Russian Jews went from relative isolation to being highly integrated into the new Soviet culture and society, while retaining a strong ethnic and cultural identity. This identity took shape during the 1920s and 1930s, when the government attempted to create a new Jewish culture, national in form and socialist in content. Soviet and Kosher is the first study of key Yiddish documents that brought these Soviet messages to Jews, notably the Red Haggadah, a Soviet parody of the traditional Passover manual; songs about Lenin and Stalin; scripts from regional theaters; Socialist Realist fiction; and magazines for children and adults. More than 200 interviews conducted by the author in Russia, Germany, and the United States testify to the reception of these cultural products and provide a unique portrait of the cultural life of the average Soviet Jew.